Accentuated Decrease in Social Interaction in Rats Subjected to Repeated Ethanol Withdrawals - Overstreet, David H. (2002)
BACKGROUND: Previous work has shown that repeated withdrawals from chronic ethanol exposure can kindle seizures in rodents. In this article, the effects of a three-cycle model of ethanol exposure and withdrawal on the social interaction test of anxiety are summarized. METHODS: Rats were exposed to ethanol (7% or 4.5%) diets over three periods of 5 days, with 2 days of withdrawal between cycles. Between 5 and 6 hr after the ethanol was removed, pairs of rats were placed in open field chambers for the assessment of social interaction behavior and locomotor activity. RESULTS: After the third cycle of ethanol (7%) presentation, both male and female rats exhibited lower social interaction behavior (more anxiety) and activity than after a single cycle. Rats exposed to a similar amount of ethanol but tested while ethanol was still available did not exhibit a reduction in social interaction. The decrease in social interaction was still present for up to 24 hr but had disappeared by 48 hr after ethanol was withdrawn. When rats were allowed 8 or 16 days to recover from the effects of the three-cycle protocol, a further exposure to 5 days of 7% ethanol diet resulted in a reduction in social interaction on withdrawal similar to that seen from the three-cycle protocol. In contrast, rats exposed continuously to 7% ethanol diet for 15 consecutive days exhibited higher levels of social interaction when maintained on control diet for 8 or 16 days and then reexposed to ethanol. Rats that were exposed to the three-cycle protocol and allowed 32 days to recover before being reexposed to ethanol still had a partial deficit in social interaction. Finally, animals subjected to repeated withdrawals from 4.5% ethanol exhibited a reduction in social interaction without a change in activity after the final withdrawal from ethanol, whereas rats exposed continuously to a 4.5% ethanol diet did not exhibit a reduction in social interaction or activity. Neither blood ethanol concentrations nor changes in body weight could account for these behavioral differences. CONCLUSION: Repeated withdrawal from ethanol can lead to accentuated or more persistent anxiety-like behavior in rats, as indicated by a decrease in social interaction. The withdrawal-induced decrease in locomotor activity is not accentuated by repeated withdrawals. This model of repeated withdrawals from ethanol may prove useful in defining the neurochemical basis of this accentuation.